Happiness and economics : how the economy and institutions affect well-being - Frey, Bruno S.; Stutzer, Alois (Princeton, N.J. : Princeton University Press, 2002)
Offers a link between happiness and economics - and between happiness and democracy. iT demonstrates how micro- and macro-economic conditions in the form of income, unemployment, and inflation affect happiness. It shows that the more developed the democratic institutions and the degree of local autonomy, the more satisfied people are.
Includes bibliographical references (p. [195]-214) and index.
oif 31/07/14
Loan
Keywords: Economics; Economics -- Psychological aspects; Happiness -- Economic aspects; Well-being.